Right Holders or Control Objects? : The Process of Government Intervention with Unaccompanied Migrant Children and Adolescents in Cádiz (Spain) and Tapachula (Mexico) - Machín Álvarez, Macarena (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
This article analyzes the actions of the authorities with respect to unaccompanied migrant children in Cádiz (Spain) and Tapachula (Mexico), two specific contexts of location of this group that, although they share similarities in migration and protection of the rights of children, present different solutions in a prevalent way: in Cádiz prevails the permanence of unaccompanied migrant children under the protection of the State while, in Tapachula, it predominates the return to their countries of origin and the possible putting at risk their physical and psychological integrity. Beyond the particular case that is addressed, it is proposed to compare the influence that the different ways of resolving the authorities have on access and closure of the rights of this group. For this, it has been collected the opinion of 50 key informants distributed in both context, systematized according to the possible common and specific trajectories that arise in each of the context and grouped into six itineraries-type of intervention based on certain criteria obtained of the rights-based approach of children. In terms of results, this comparative case study makes it possible to unravel the complexities of the intervention models with this population, it confirmed that despite being different models (tutelary versus security) in practice, in both cases, full exercise of the rights is hindered and denied to this group being that an adultcentric-statecentric approach prevails to the detriment of an infant-centered or one based on the best interest of the child.